Acquired resistance to erlotinib in EGFR mutation-positive lung adenocarcinoma among Hispanics (CLICaP) (2017)
Lung cancer harboring epidermal growth factor receptor (EGFR) mutations and treated with EGFR tyrosine kinase inhibitors (TKIs) all eventually develop acquired resistance to the treatment, with half of the patients developing EGFR T790M resistance mutations. The purpose of this study was to assess histological and clinical characteristics and survival outcomes in Hispanic EGFR mutated lung cancer patients after disease progression. Patients and methods: EGFR mutation-positive lung cancer patients (n = 34) with acquired resistance to the EGFR-TKI erlotinib were identified from 2011 to 2015. Post-progression tumor specimens were collected for molecular analysis. Post-progression interventions, response to treatment, and survival were assessed and compared among all patients and those with and without T790M mutations. Mean age was 59.4 ± 13.9 years, 65% were never-smokers, and 53% had a performance status 0-1. All patients received erlotinib as first-line treatment. Identified mutations included: 60% DelE19 (Del746-750) and 40% L858R. First-line erlotinib overall response rate (ORR) was 61.8% and progression free survival (PFS) was 16.8 months (95% CI: 13.7-19.9). Acquired resistance mutations identified were T790M mutation (47.1%); PI3K mutations (14.7%); EGFR amplification (14.7%); KRAS mutation (5.9%); MET amplification (8.8%); HER2 alterations (5.9%, deletions/insertions in e20); and SCLC transformation (2.9%). Of patients, 79.4% received treatment after progression. ORR for post-erlotinib treatment was 47.1% (CR 2/PR 14) and median PFS was 8.3 months (95% CI: 2.2-36.6). Median overall survival (OS) from treatment initiation was 32.9 months (95% CI: 30.4-35.3), and only the use of post-progression therapy affected OS in a multivariate analysis (p = 0.05). Hispanic patients with acquired resistance to erlotinib continued to be sensitive to other treatments after progression. The proportion of T790M+ patients appears to be similar to that previously reported in Caucasians.